Pembuatan media literasi kelas awal bagi guru di Kota Makassar - Syamsiah D; Rosdiah Salam; Widya Karmila Sari Achmad (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Observations in various elementary schools both inthe district and in the city of Makassar, especially in ClusterIV in Makassar district, the teachers in teaching were uselimited learning media which resulted in students being lesscritical, creative and active. This causes students to be slow inreading and writing. The subject of this study is the primaryschool teachers in Cluster IV of KKG Makassar district inMakassar. The purpose of this community service activity ingeneral is to increase teachers' knowledge and skills in makingliteracy media that can create a critical, creative, and activelearning atmosphere. Specifically, this program aims (1) tofind out how far the teacher's ability to make literacy mediacan be used in reading and writing learning for students (first,second, and third grade); (2) to find out the opinion of theteachers about making literacy media in reading and writingfor students. The activities that have been carried out haveshown maximum results. The Big Book media making trainingprovides advantages, especially in literacy learning, namelyreading and writing.